2019
DOI: 10.1103/physrevlett.122.225701
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transitions of Hybrid Perovskites Simulated by Machine-Learning Force Fields Trained on the Fly with Bayesian Inference

Abstract: Realistic finite temperature simulations of matter are a formidable challenge for first principles methods. Long simulation times and large length scales are required, demanding years of compute time. Here we present an on-the-fly machine learning scheme that generates force fields automatically during molecular dynamics simulations. This opens up the required time and length scales, while retaining the distinctive chemical precision of first principles methods and minimizing the need for human intervention. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
402
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 388 publications
(413 citation statements)
references
References 47 publications
(42 reference statements)
8
402
2
1
Order By: Relevance
“…The machine-learned force field (MLFF) of MAPbI 3 as presented in Ref. 45 is used to generate MD trajectories. The MLFF was trained on-the-fly during FPMD calculations with the SCAN (Strongly Constrained Appropriately Normed) 53 exchange-correlation functional, as its relative total energies agree well with many-body perturbation theory calculations in random phase approximation 54 .…”
Section: Molecular Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The machine-learned force field (MLFF) of MAPbI 3 as presented in Ref. 45 is used to generate MD trajectories. The MLFF was trained on-the-fly during FPMD calculations with the SCAN (Strongly Constrained Appropriately Normed) 53 exchange-correlation functional, as its relative total energies agree well with many-body perturbation theory calculations in random phase approximation 54 .…”
Section: Molecular Dynamicsmentioning
confidence: 99%
“…In order to straightforwardly compare the ordering patterns of the MA molecules we calculate the molecular order parameter as briefly presented Ref. 45 . We assume an integer cubic grid q = (i, j, k) of dimensions N = N x × N y × N z that has on each site a unit vector p q describing the orientation of the MA molecule.…”
Section: A Molecular Order Parametermentioning
confidence: 99%
“…Podryabinkin et al showed that their approach can identify various existing and hypothetical boron allotropes 20 . Finally, Jinnouchi et al demonstrated how ab initio molecular dynamics (AIMD) simulations of specific systems can be sped up by active learning of the computed forces (in a modified GAP framework), using the predicted error of the Gaussian process to select new datapoints and to improve the speed of AIMD 37,39 .…”
Section: Introductionmentioning
confidence: 99%
“…We also mention on-the-fly or "onlinetrained" ML potentials: [80][81][82] these start with a quantummechanical (again, normally DFT-based) MD simulation and train an ML potential while the simulation is being run. We also mention on-the-fly or "onlinetrained" ML potentials: [80][81][82] these start with a quantummechanical (again, normally DFT-based) MD simulation and train an ML potential while the simulation is being run.…”
Section: Ingredient 3: Regression Tools and Implementationsmentioning
confidence: 99%